Pandangan generasi muda terhadap upacara perkawinan adat di Kota Medan - Pelawi, Kencana Sembiring; Kartikasari, Tatiek (Jakarta : Departemen Pendidikan dan Kebudayaan, 1998)
Attitude toward traditional marriage among the youth in Medan, Sumatera Utara Province.
Keywords: Marriage customs and rites -- Indonesia -- Medan; Youth -- Indonesia -- Medan -- Attitudes